Effect of N on the microstructure and magnetic properties of FePdSi nanocomposite films. (16th January 2019) - He, Mufen; Ma, Lei; Zhou, Xin; Liu, Tao; Li, Lin; Yao, Qingrong; Gu, Zhengfei
Abstract: FePdSi and FePdSiN nanocomposite films were fabricated successfully on quartz glass substrate by direct current reactive magnetron sputtering. Under the same preparation parameters, the Fe/Pd ratio of FePdSi and FePdSiN films was unbalanced, which emerged obvious difference in morphology, microstructure and magnetic properties. The addition of N played an important role on the molecular free path and sputtering rate of Fe–Pd–Si film. Preferential combination of N with Si formed an amorphous Si–N matrix between the FePd nanoparticles, which improved the coercivity, maximum magnetic energy product and remanence ratio up to 2.8 kOe, 9.4 MGOe and 0.99 after thermal treatment at 550 °C, respectively. The mechanism was proposed to account for this unique growth technique.